Screening Options in Autism Telediagnosis: Examination of TAP, M-CHAT-R, and DCI Concordance and Predictive Value in a Telediagnostic Model. - Weitlauf, Amy S.; Foster, Tori; Slaughter, James C.; Fleck, Mary; Harris, Jill; Coffield, Caroline; Simcoe, Kathleen; Baggett, Jenny; Stainbrook, Alacia; Warren, Zachary E. (Journal of Autism & Developmental Disorders, 2025)
Tele-assessment of autism in early childhood has increased. However, it is unclear how autism screening tools (M-CHAT-R, DCI) function as part of tele-assessment and relate to a commonly used tele-assessment instrument, the TAP. 361 families from a clinically referred sample of children (mean age: 27.63 months, sd = 4.86 months) completed the M-CHAT-R and DCI prior to a tele-assessment visit utilizing the TAP. Data was collected on demographic background, measure scores, and diagnostic outcome. No significant differences in measure scores or diagnostic findings emerged in age at referral, age group, age at diagnosis, or child sex, ethnicity, or racial background. The M-CHAT-R and DCI correlated strongly and positively. Older age was associated with lower risk scores on screening instruments. Children with autism had significantly higher scores on all screener and subdomain scores, with the exception of DCI Behavior. Subdomains of the DCI emerged as the strongest predictor of diagnostic outcome. Both the DCI total score and the M-CHAT-R significantly related to diagnostic outcome and TAP score in this tele-assessment model, regardless of child age or sex. Findings also support use of the DCI for children under 24 months of age.